PROSPECTS FOR THE DEVELOPMENT OF UZBEKISTAN’S EXPORTS IN THE CONTEXT OF ACCESSION TO THE WTO - Gulyamova Gulshakhnoz; Nurmukhammadov Islombek (Modern American Journals, 2025)
The article examines the prospects for the export development of Uzbekistan against the backdrop of the active phase of negotiations on accession to the World Trade Organization (WTO). Based on official statistical data and WTO documents, the study analyzes the current state of exports, the expected effects of accession, institutional and regulatory reforms (SPS/TBT, technical regulation, trade facilitation), as well as sectoral directions of deep processing and diversification. The experience of regional countries (Kazakhstan, Kyrgyzstan) is compared. Practical recommendations for government bodies and businesses are formulated. The main conclusions are as follows: accession to the WTO can accelerate the structural shift from raw material to non-raw material exports, expand access to markets and investments, provided that the system of standards and quality infrastructure is modernized in parallel, along with targeted support for exporters.
Keywords: WTO, export, Uzbekistan, trade liberalization, SPS, TBT, technical regulation, trade facilitation, diversification.